Daño punitivo : prevención y justicia en el derecho de los consumidores - Brodsky, Jonathan Matías (2012)
This paper deals with punitive damages, very recently comprised in the\nConsumer Protection Act through its last reform. On one hand, we will address the\nissue whether they belong to civil law (as the regulation in force establishes) or to criminal\nlaw, depending on the very purpose of the institution. On the other hand, we will\nexamine the diverse aspects of their legal regulation, according to the aims of punitive\ndamages and their relevance in the consumer relationship